Isolation and Characterization of Local Microorganisms (MOL) of Bamboo Shoots (Dendrocalamus asper) and Its Effect on the Growth of Pakcoy Plants (Brassica rapa L.) - Mariatil Kabatia; Annisa Khumaira; Arif Bimantara (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
MOL is an organic fertilizer made from fermented natural materials that contain carbohydrates and many macro and micro nutrients. This type of fertilizer also contains microorganisms that its contribute towards role as biofertilizer. One potential organic material for MOL that is easily available is bamboo shoots. Bamboo shoots contain important nutrients which can improve plant growth and development. The purpose of this study was to determine what bacteria are contained in bamboo shoot MOL and to determine its effect on growth in pakcoy plants (Brassica rapa L). This research is an experimental study using RAL (Complete Randomized Design), including: isolation and characterization of bamboo shoot MOL, application of MOL to pakcoy plants (Brassica rapa L) containing bacterial isolates from bamboo shoot MOL. The observed parameters include plant height, root length, number of leaves and wet weight of pakcoy plants followed by statistical analysis using analysis of variance (ANOVA) and characterization results on isolates obtained based on Bergey's Manual of Determinative Bacteriology. From the research results obtained that the prediction of the genus of bacteria contained in bamboo shoots is Lactobacillus, Streptococcus Sp, Saccharococcus, Veillonella sp, Azotobacter, and Rhizobacter which play a role in accelerating decomposition so as to produce the best quality fertilizer and MOL contained in bamboo shoots has a significant effect on the growth of pakcoy (Brassica rapa L). The best result for MOL bamboo shoots that are good for pakcoy plant growth is obtained at a concentration of 150ml / L so that MOL bamboo shoots have the potential for pakcoy plant growth.